Mastering C# concurrency : create robust and scalable applications, along with responsive UI, using concurrency and the multi-threading infrastructure in .NET and C# /: create robust and scalable applications, along with responsive UI, using concurrency and the multi-threading infrastructure in .NET and C#. (2015) - Agafonov, Eugene; Koryavchenko, Andrew
No abstract available